Implementasi Pengelolaan Data Sektoral Melalui Dashboard Satu Data Provinsi Sumatera Selatan Pada Sekretariat DPRD Provinsi Sumatera Selatan - Intan Mervinasari; Gusmelia Testiana (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
Digital transformation has encouraged government institutions to improve data management as a foundation for decision-making and public service delivery. One of its implementations is the One Data Indonesia program, which is supported through the South Sumatra One Data Dashboard based on the Comprehensive Knowledge Archive Network (CKAN). This article aims to describe the implementation of sectoral data management at the Secretariat of the Regional House of Representatives (DPRD) of South Sumatra Province during the internship program. This study employed a descriptive qualitative approach, with data collected through observation, documentation, and direct participation in each stage of the data management process. The results indicate that the internship activities involved data collection, data inspection, verification, validation, metadata preparation, and data entry into the One Data Dashboard. Of the five data indicators managed by the Secretariat of the DPRD of South Sumatra Province, four indicators were available and successfully processed, while one indicator, namely the number of DPRD agendas facilitated according to schedule, could not be uploaded because the data were unavailable during the internship period. The internship provided practical experience in sectoral data management while supporting the implementation of data management at the Secretariat of the DPRD of South Sumatra Province through the utilization of the CKAN-based One Data Dashboard.